Girls in power : gender, body, and menstruation in adolescence - Fingerson, Laura (State University of New York Press, 2006)
Girls in Power offers a fascinating and unique look at the social aspects of menstruation in the lives of adolescent girls--and also in the lives of adolescent boys. Although there has been much research on other aspects of gender and the body, this is one of the few books to examine menstruation and the first to explore how it plays a part in power interactions between boys and girls. Talking openly in single- and mixed-gender settings, individuals and groups of high school-age girls and boys share their interpretations and experiences of menstruation. Author Laura Fingerson reveals that while teens have negative feelings about menstruation, teen girls use their experiences of menstruation as a source of embodied power in their interactions with other girls and with boys. She also explores how boys deal with their own reduced power. The book extends our theoretical and analytical understanding of youth, gender, power, and embodiment by providing a more balanced view of adolescent social life.